Transferring Tacit Know-How: Do Opportunism Safeguards Matter for Firm Boundary Decisions? - Eapen, Alex; Krishnan, Rekha (Organization Science, 2019)
In recent years, scholars have demonstrated that capability theories of firm boundaries are fundamentally intertwined with contractual arguments. A productive use of capability arguments, therefore, is when they are joined with contractual ones in an integrated theory of the firm. However, contractual and capability scholars have traditionally held incommensurable views on the relevance of opportunism safeguards for a theory of the firm. Sponsors of the contractual view treat opportunism safeguards as fundamental, whereas several scholars in the knowledge-based strand of the capabilities camp consider it redundant. Moreover, in several recent integrative efforts, opportunism and safeguarding against it feature as linchpin theoretical ideas. To fully integrate contractual and capability theories, therefore, there is a need to resolve this point of incommensurability. We revisit a specific problem in the international strategy literature where the opportunism debate has been significant—the transfer of tacit know-how by multinational firms—and employ moderator-effect hypotheses to test two alternative mechanisms for why tacit know-how is transferred internally. We test whether tacit know-how is transferred internally to safeguard against opportunism or, alternatively, to avail the coordination benefits of common routines within firms. Our results indicate the former and not the latter, and thereby support a cornerstone notion in recent efforts toward an integrated theory of the firm.